A novel active auxiliary circuit for efficiency enhancement integrated with synchronous buck converter. (27th April 2016) - Panda, Anup Kumar; Sarode, Shiva; Tejavathu, Ramesh
Summary: In this paper, a novel auxiliary circuit is introduced for the synchronous buck converter. This auxiliary circuit provides zero‐current, zero‐voltage switching conditions for the main and synchronous switches while providing zero‐current condition for the auxiliary switch and diodes. The proposed active auxiliary circuit integrated with synchronous buck converter that emanates to zero‐voltage transition (ZVT)–zero‐current transition (ZCT) pulse width‐modulated (PWM) synchronous buck converter is analyzed, and its operating modes are presented. The additional voltage and current stresses on main, synchronous and auxiliary switches get decimated because of the resonance of the auxiliary circuit that acts for a small segment of time in the proposed converter. The important design feature of soft‐switching converters is the placement of resonant components that mollifies the switching and conduction losses. With the advent of ZVT–ZCT switching, there is an increase in the switching frequency that declines the resonant component values in the converters and also constricts the switching losses. The characteristics of the proposed converter are verified with the simulation in the Power Sim (PSIM) software co‐simulated with MATLAB/SIMULINK environment and implemented experimentally. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, a novel active auxiliary circuit integrated with synchronous buck converter is proposed. The proposed auxiliary circuit provides zero‐current, zero‐voltage switching conditions for the main and synchronous switches while providing zero‐current condition for the auxiliary switch and diodes. The additional voltage and current stresses on main, synchronous and auxiliary switches get decimated because of the resonance of the auxiliary circuit that acts for small segment of time in the proposed converter.